东盟中文学习者画作中的中文教师角色：基于隐喻的分析 - Meng Xiaofeng; Song Yanjie (Sinolingua: Journal of Chinese Studies, 2024)
With the implementation and promotion of the "Belt and Road" initiative, economic and trade cooperation and humanistic exchanges between China and ASEAN are going deeper, and Chinese language education in ASEAN has shown a booming development. As a core participant of international Chinese language education in the region, the role of Chinese language teachers is an important conceptual source of ASEAN youth's perception of China, which has a crucial impact on Chinese language learners. Based on the creation of visual metaphors, this study uses the teacher metaphor analysis framework to summarize the ASEAN Chinese teacher role metaphor categories and explore the ASEAN Chinese teacher traits from the learners' perspective. We selected 60 graphic works created by ASEAN Chinese learners as the research material, extracted 31 Chinese teacher role metaphors, and delineated six metaphorical conceptual categories. This study aims to arouse the attention of international Chinese teacher educators, social organizations, and Chinese teachers themselves to the developmental changes of Chinese teacher roles, and to provide a reference for the professional development of international Chinese teachers.